Introduced cats (Felis catus) eating a continental fauna: The number of mammals killed in Australia. (September 2019) - Murphy, Brett P.; Woolley, Leigh-Ann; Geyle, Hayley M.; Legge, Sarah M.; Palmer, Russell; Dickman, Chris R.; Augusteyn, John; Brown, Stuart C.; Comer, Sarah; Doherty, Tim S.; Eager, Charlie; Edwards, Glenn; et al.
Abstract: Predation by cats ( Felis catus ) is implicated in the decline and extinction of many Australian mammal species. We estimate the number of mammals killed by cats across Australia through meta-analysis of data on the frequency of mammals in cat diet samples from 107 studies. For feral cats in largely natural landscapes, the spatially-weighted mean frequency of mammals in diet samples was 70% (44% for native species, 34% for introduced species). Frequency was significantly higher on the mainland, and in areas of low temperature and topographic ruggedness. Geographic patterns varied markedly between native and introduced mammals, with native mammals most frequent in northern Australia. We estimate that: (i) 815 million individuals yr −1 are killed by feral cats in natural landscapes, 56% of which are native species; (ii) 149 million individuals yr −1 are killed by unowned cats in highly modified landscapes; and (iii) 180 million individuals yr −1 are killed by pet cats. For the latter two components, mainly introduced species are killed. Collectively, across the three components of the cat population, 1, 144 million individuals yr −1 are killed by cats, of which, at least 40% (459 million individuals yr −1 ) are native species. It remains challenging to interpret this tally in terms of its impact on population viability for Australian mammals, because demographic information is not available for most species. However, our estimate of annual mammal mortality due to cat predation is substantially higher than that due to another key threatening process, land clearing.